Rings at the Wrong Place: Acute Penile Incarceration, A Case Report and Review of Treatment Options - Sharma, Pritam; Iyyan, Bhalaguru; Pillai, Sunil; Hedge, Padmaraj (Asian Journal of Medical Sciences, 2013)
Penile strangulation and entrapment is an unusual acute urologic emergency with a potential for serious complication. It can occur in adults and children. Penile incarceration from metallic and non-metallic objects has been reported since 1755. Patients present with various grades of penile injury & treatment varies with the grade at presentation. Removal of the offending objects can be cumbersome and tricky at times. We present a case and review the treatment options in such situations. Asian Journal of Medical Science, Volume-4 (2013), Pages 40-43 DOI: http://dx.doi.org/10.3126/ajms.v4i4.7641